Health education for first-ever stroke on sick role acceptance and performance of activities of daily living - Ereno, Gina Marie Pacho
Sick role acceptance as a determinant to the acceptance of one's illness and determination to get well as studied among stroke patients. It is considered to be the cornerstone of healthy personality and psychological wellness in the course of a chronic illness such as stroke. It is a conviction that one is competent to live and worthy of living in spite of limitations and disabilities. Ability of the patients to perform activities of daily living efficiently and independently promotes quality of life as they go back to their respective homes and communities and care for themselves after hospitalization.This study utilized HEFES (Health Education for First-Ever Stroke) as an intervention. The study sought to achieve three (3) objectives: to determine the effect of HEFES on sick role acceptance and performance of activities of daily living; to determine the relationship between sick role acceptance and performance of activities of daily living among first-ever stroke patients; and to determine whether patient factors are related to sick role acceptance and performance of activities of daily living.This study utilized the post-test only control group design, wherein one group had undergone experimental treatment and post-test, while the other group had post-test only. Forty (40) first-ever stroke participated in this study. The data collection was done in two hospitals: Philippine General Hospital and Eas Avenue Medical Center. There were three (3) instruments used in this study.First, the Patient's Data, an original questionnaire on patient factors such as age, sex, civil status, education, family support and presence/absence of comorbid processes. Second, the SRA Profile, was adopted and modified from the ones formulated by Julia S. Brown and May E. Rawlinson. Finally, the third is the ADL Multidimensional Evaluation Checklist was modified for the study basing from the three standardized functional assessment tools: Katz Index of Activities of Daily Living; Barthel Index and the OARS MFAQ.HEFES is a health education program for first-ever stroke patients designed to promote positive sick role acceptance and performance of activities of daily living. It consists of a series of patient education that is interactive and personalizaed given individually to patients in the study group. It's main objective is to increase the knowledge and understanding of first-ever stroke patients regarding their illness. It also includes discussion about the psychological and emotional aspect of illness, which helped them adjust and accept their limitations and disabilities.The findings of the study revealed the following data. Majority of the patients (72.5) belonged to the middle age group. The mean age of the patients was 49.8 years (SD - 11.382). There were more males (n - 27) than females (n - 13). Generally, the patients were married (80).